Captivity, Masculinity and Degradation in an Early Rabbinic Tale - Daum, Robert A. (2014)
This article examines differences between versions of an erotic Rabbinic narrative about rescuing a captive boy, who had been carried away from Roman-occupied Jerusalem and was enduring (or facing) sexual exploitation at the hands of Roman captors. A synoptic reading suggests a pattern of retroactive "touching up" of scandalous elements in early versions of the tale by the time it appears in early medieval manuscripts of the Babylonian Talmud. These changes soften the scandalous implications of a sophisticated Palestinian Jewish appropriation of an Ancient Near Eastern and Greco-Roman homoerotic narrative. The comparatively inelegant later version suggests efforts to de-eroticize the plot, masculinize the captive, and lessen his degradation. Literary and archaeological evidence suggests that these changes might have been motivated by the fact that in earlier versions the captive was anonymous, whilst in later versions he is identified as a pillar of the talmudic tradition.
Keywords: Rabbi Ishmael; Rabbi Joshua; Rome; Talmud; captivity; homoerotic; Masculinity; Rabbinic; Ransom; sexual degradation